P2.150 Patterns of STI Clinic Utilization Among Non-Migrant and Migrant Female Sex Workers in Karnataka, India. (13th July 2013) - Becker, M L; Mishra, S; Ramanaik, S; Halli, S; Blanchard, J
Abstract : Background: Efforts to provide screening or treatment of sexually transmitted infections (STIs) among female sex workers (FSWs) require adequate access and uptake of STI-specific health services; this is especially relevant for female sex workers who migrate for work. We examined the patterns of STI clinic use among non-migrant and migrant FSWs in Karnataka, India. Methods: We used baseline data on 728 non-migrant and 833 migrant FSWs enrolled in a cohort study of FSWs in Karnataka in 2008. The pattern of local (defined as the FSW's place of origin) and destination STI clinic utilisation by migration status of FSWs was examined using univariate and multivariate logistic regression. Results: Overall, 77.9% and 64.5% of non-migrant and migrant FSWs had ever attended a local STI clinic (p < 0.001). Irrespective of migration status, local sex work was associated with local STI clinic attendance (AOR, 2.9; 95% CI: 2.3–3.7), and did not vary by other characteristics of sex work. Local clinic attendance was also higher among FSWs who demonstrated awareness of local HIV/STI prevention programmes (AOR 4.7; 95% CI: 3.3–6.5). Only 33.0% of migrant FSWs who engaged in local sex work had attended an STI clinic in their destination city, compared to 63.8% of migrant FSWs who did not participate in local sex work (p < 0.001). However multivariate analysis indicated that the association between local sex work and a destination clinic visit was mediated by a lack of awareness of prevention programmes at destination and shorter (< 1 month) destination visits. Local clinic attendance remained independently associated with destination clinic visits (AOR 2.8; 95% CI: 1.8–4.2). Conclusion: Although local STI clinic attendance by FSWs is high, destination clinic visits among migrant FSWs remains low in the presence of local sex work. The findings call for linkages between local and destination HIV/STI prevention programmes to optimise STI-service delivery to migrant FSWs.